Multi-scale numerical analysis and experimental verification for nano-cutting. (November 2021) - Yang, Shuming; Cheng, Biyao; McGeough, Joseph A.; Woldu, Yonas Tesfaye; Yang, Xiaokai
Abstract: The development of numerical models applicable to ultra-precision machining presents serious challenges. Molecular dynamics methods can effectively capture nano-cutting operations at the micro-nanoscale but fail to accurately capture the realistically large-scale deformations involved in material removal, while it can be addressed by finite element methods but lacks the precision required for modeling nanoscale behaviors. The present study addresses this issue by developing a multi-scale numerical modeling method, the optimized Quasicontinuum (QC) method. Compared with the original QC method, the optimized QC method adds the material removal function, avoids unreasonable lattice excessive distortion and large-area, deep dislocation slip. The optimized QC method can more truly simulate the large deformation and material removal phenomenon of cutting, and greatly improve the calculation speed. The influence of cutting parameters such as cutting depth, tool rake angle and rounded tool cutting edge radius on cutting force is studied. The change of cutting depth has the most significant influence on cutting force, while the influence of tool rake angle and rounded tool cutting edge radius are relatively small. Therefore, the effect of cutting depth on cutting force is studied through the experiment of single crystal copper nano-cutting to verify the effectiveness of multi-scale method. The experimental results show that it is proportional to the simulation results. Highlights: The multi-scale simulation QC method is optimized. The material removal function is added, and the calculation time is shortened. A multi-scale cutting model of single crystal copper is established. The influence of cutting parameters on ultra-precision cutting force is studied. The experimental results are proportionally correlated with the simulation results.